Covid-19 Policies: Human Rights Approaches to Protecting Vulnerable Groups in Africa - Chavarro, Diego; Kagaha, Alexander; Kaunda, Blessings; Zakumumpa, Henry; Manderson, Lenore (Africa Academic Science, 2021)
Multiple social interventions have been introduced to contain the COVID-19 pandemic across Africa. These policies have caused school and workplace closures, controlled informal work activities, led to the cancellation of many public events, restricted the size of public and private gatherings (including religious congregations, weddings and funerals), suspended public transport, limited travel, imposed curfews, and required contact tracing. In anticipation of negative economic impacts of these measures, many governments introduced cash transfers, social pensions, food aid, utility and tax waivers and related measures. However, people living precariously and/or in a structurally vulnerable position have not always had access to this support, and the measures imposed to contain and mitigate the pandemic did not take sufficient account of the effects of the human rights of these individuals. The pandemic is too recent for much empirical research on the impacts of COVID-19, or on the effect of interventions to protect human rights. In undertaking a rapid review of these questions, we examined primary studies, editorial notes, opinion papers and literature reviews using mainly qualitative approaches, and discussions of quantitative studies where these contribute to further understanding the impacts of interventions on human rights in Africa. In this synthesis and analysis, we contribute to understanding how social interventions impact the human rights of vulnerable populations and identify proposals for a policy response to COVID-19 that better integrates the needs of these populations in Africa.